2017
DOI: 10.21037/jgo.2017.01.24
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine and capecitabine for advanced biliary cancer

Abstract: Background: Gemcitabine with capecitabine (gem-cap) is an established regimen for advanced biliary cancer (ABC) supported by our previously reported phase II trial. Here, we provide our updated experience. (69/129) experienced a grade 3/4 toxicity. The most common (35.7%) was a hematologic toxicity (neutropenia or thrombocytopenia) followed by infection (25.6%). Conclusions: Gem-cap provides similar survival outcomes to gemcitabine/cisplatin based on historical comparison to the ABC-2 trial (median PFS =8.0 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Gemcitabine is used for patients with advanced-stage CCA in current clinical practice. [24][25][26] Our IC 50 analysis in CCLP1 and HuCCT1 cells revealed that LINC01714 could enhance the drug sensitivity of gemcitabine in CCA cells. Moreover, LINC01714 exerts its impact on gemcitabine through interaction with FOXO3 phosphorylation.…”
Section: Discussionmentioning
confidence: 84%
“…Gemcitabine is used for patients with advanced-stage CCA in current clinical practice. [24][25][26] Our IC 50 analysis in CCLP1 and HuCCT1 cells revealed that LINC01714 could enhance the drug sensitivity of gemcitabine in CCA cells. Moreover, LINC01714 exerts its impact on gemcitabine through interaction with FOXO3 phosphorylation.…”
Section: Discussionmentioning
confidence: 84%
“…But a few recent studies showed a slight survival gain 18. Gabriel et al19 reported that gemcitabine plus cisplatin for biliary cancer provided survival benefit. Moureau-Zabotto et al reported that the conformal-3D external-beam-radiotherapy (EBRT) seemed efficient to treat locally-advanced and unresectable extrahepatic cholangiocarcinomas, with acceptable toxicity 20…”
Section: Discussionmentioning
confidence: 99%
“…In such cases the current conservative treatment strategies with application of radiotherapy, systemic and regional chemotherapy attract firstly by their relative safety and by increasing effectiveness [6,7,8]. Combination of gemcitabine, cisplatin and nab-paclitaxel allowed to reach a partial answer to therapy in 45% of cases [9].…”
Section: Discussionmentioning
confidence: 99%